Interleukin-37 mediates the anti-oral tumor activity in oral cancer through STAT3 - Fang Jing; Li Kunshan; Zhang Liyuan; Zhang Ying; Wang Yifan; Zhang Jing (Open Medicine)
Oral cancer constitutes a significant public health challenge, and gaining insights into the pathogenesis of oral cancer is crucial for the development of innovative therapeutic approaches. To address this objective, this study investigates the impact of interleukin-37 (IL-37) on oral cancer and its underlying mechanisms. Two oral cancer cell lines, HN13 and HSC-6, were employed in the study. Our findings reveal that IL-37 markedly inhibits cell viability and induces apoptosis in oral cancer cells. IL-37 attenuates the proliferation of oral cancer cells induced by lipopolysaccharide and tumor necrosis factor-alpha, while knockdown of IL-37 exacerbates this induction. Furthermore, IL-37 demonstrates anti-inflammatory effects on oral cancer cells. The modulation of inflammation, proliferation, apoptosis, and migration by IL-37 is mediated through the STAT3 pathway. The outcomes of this study contribute valuable insights to a deeper understanding of oral cancer pathogenesis and pave the way for the development of novel drugs for the treatment of this disease.